Developments in the Ni–Nb–Zr amorphous alloy membranes - Sarker, S.; Chandra, D.; Hirscher, M.; Dolan, M.; Isheim, D.; Wermer, J.; Viano, D.; Baricco, M.; Udovic, T.J.; Grant, D.; Palumbo, O.; Paolone, A.; et al. (Springer Verlag, 2016)
Most of the global H2 production is derived from hydrocarbon-based fuels, and efficient H2/CO2 separation is necessary to deliver a high-purity H2 product. Hydrogen-selective alloy membranes are emerging as a viable alternative to traditional pressure swing adsorption processes as a means for H2/CO2 separation. These membranes can be formed from a wide range of alloys, and those based on Pd are the closest to commercial deployment. The high cost of Pd (USD *31,000 kg-1) is driving the development of less-expensive alternatives, including inexpensive amorphous (Ni60Nb40)100-xZrx alloys. Amorphous alloy membranes can be fabricated directly from the molten state into continuous ribbons via melt spinning and depending on the composition can exhibit relatively high hydrogen permeability between 473 and 673 K. Here we review recent developments in these low-cost membrane materials, especially with respect to permeation behavior, electrical transport properties, and understanding of local atomic order. To further understand the nature of these solids, atom probe tomography has been performed, revealing amorphous Nb-rich and Zr-rich clusters embedded in majority Ni matrix whose compositions deviated from the nominal overall composition of the membrane.